Hermann Karl von Keyserlingk and the Recognition of the Russian Imperial Title by the Holy Roman Empire in 1745–1746 - M. A. Petrova (Vestnik MGIMO-Universiteta)
The article, based on the unpublished documents from the Archive of the Foreign Policy of the Russian Empire, reveals for the first time details of a little-known episode in the history of the Russian diplomatic service – the mission of Empress' Elisabeth I minister plenipotentiary Count of Courland Hermann Karl von Keyserlingk to Frankfurt am Main and Regensburg during the War of the Austrian Succession. The mission's goal was to achieve recognition of the Russian imperial title from the Emperor of the Holy Roman Empire. The author managed to find out, it was Keyserlingk who had the idea to send the official representative of Russia to the election of the Emperor in Frankfurt in 1745 and then in 1746 to the Imperial Diet in Regensburg, which approved the election results. Keyserlingk proposed the most straightforward plan that did not damage the prestige of Elisabeth I – to transfer the credentials with the imperial title to the College of Electors and to receive a recreditive (leave-letter), trying to get the title included in the text. The same should have been done at the Imperial Diet. The main task of the diplomat was to prevent the issue of the title from becoming the subject of discussion at meetings of the College of Electors and at the Diet, since the details of the discussion would undoubtedly get into the official documents of these institutions and become public. The moment for solving this delicate issue turned out to be a good one: the continued hostilities forced the Imperial Estates to seek help from Russia. As a result, they were ready to do Elisabeth I a favor. This largely explains the success of Keyserlingk's mission, which enjoyed the support of imperial diplomats – representatives of the Electors of Mainz, Saxony, Bohemia and at the final stage – of the Elector of Brandenburg, King of Denmark and Emperor Franz I. The article also examines Keyserlingk's participation in recognizing the seventeen-year-old Grand Prince Peter as Duke of Holstein-Gottorp, a legal major a year early.